Single-cell transcriptome profiling and the use of AID deficient mice reveal that B cell activation combined with antibody class switch recombination and somatic hypermutation do not benefit the control of experimental trypanosomosis. - Hang Thi Thu Nguyen (Public Library of Science (PLoS), 2021)
Salivarian trypanosomes are extracellular protozoan parasites causing infections in a wide range of mammalian hosts, with Trypanosoma evansi having the widest geographic distribution, reaching territories far outside Africa and occasionally even Europe. Besides causing the animal diseases, T. evansi can cause atypical Human Trypanosomosis. The success of this parasite is attributed to its capacity to evade and disable the mammalian defense response. To unravel the latter, we applied here for the first time a scRNA-seq analysis on splenocytes from trypanosome infected mice, at two time points during infection, i.e. just after control of the first parasitemia peak (day 14) and a late chronic time point during infection (day 42). This analysis was combined with flow cytometry and ELISA, revealing that T. evansi induces prompt activation of splenic IgM+CD1d+ Marginal Zone and IgMIntIgD+ Follicular B cells, coinciding with an increase in plasma IgG2c Ab levels. Despite the absence of follicles, a rapid accumulation of Aicda+ GC-like B cells followed first parasitemia peak clearance, accompanied by the occurrence of Xbp1+ expressing CD138+ plasma B cells and Tbx21+ atypical CD11c+ memory B cells. Ablation of immature CD93+ bone marrow and Vpreb3+Ly6d+Ighm+ expressing transitional spleen B cells prevented mature peripheral B cell replenishment. Interestingly, AID-/- mice that lack the capacity to mount anti-parasite IgG responses, exhibited a superior defense level against T. evansi infections. Here, elevated natural IgMs were able to exert in vivo and in vitro trypanocidal activity. Hence, we conclude that in immune competent mice, trypanosomosis associated B cell activation and switched IgG production is rapidly induced by T. evansi, facilitating an escape from the detrimental natural IgM killing activity, and resulting in increased host susceptibility. This unique role of IgM and its anti-trypanosome activity are discussed in the context of the dilemma this causes for the future development of anti-trypanosome vaccines.